2007
DOI: 10.4049/jimmunol.179.12.8403
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Envelope Protein Inhibits dsRNA-Induced Innate Immune Responses

Abstract: The immune response against viral infection relies on the early production of cytokines that induce an antiviral state and trigger the activation of immune cells. This response is initiated by the recognition of virus-associated molecular patterns such as dsRNA, a viral replication intermediate recognized by TLR3 and certain RNA helicases. Infection with West Nile virus (WNV) can lead to lethal encephalitis in susceptible individuals and constitutes an emerging health threat. In this study, we report that WNV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
51
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 42 publications
1
51
0
Order By: Relevance
“…This effect is mediated at least partly by differences in viral glycosylation, since both mosquito and mammalian-cellderived viruses grown in cells that produce only high-mannose N-linked glycans are poor IFN inducers (29). The findings of studies by other groups demonstrated that N-linked glycans from C6/36-derived WNV can suppress IFN-␣/␤ induction in response to double-stranded RNA stimulation of macrophages (1) and that high-mannose residues on human immunodeficiency virus gp120 have immunosuppressive effects on DCs (30). Therefore, coinfection studies using mam-RRV and mos-RRV were performed to determine whether the poor IFN induction by mos-RRV reflected active inhibition of type I IFN induction.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…This effect is mediated at least partly by differences in viral glycosylation, since both mosquito and mammalian-cellderived viruses grown in cells that produce only high-mannose N-linked glycans are poor IFN inducers (29). The findings of studies by other groups demonstrated that N-linked glycans from C6/36-derived WNV can suppress IFN-␣/␤ induction in response to double-stranded RNA stimulation of macrophages (1) and that high-mannose residues on human immunodeficiency virus gp120 have immunosuppressive effects on DCs (30). Therefore, coinfection studies using mam-RRV and mos-RRV were performed to determine whether the poor IFN induction by mos-RRV reflected active inhibition of type I IFN induction.…”
mentioning
confidence: 61%
“…However, it is certainly possible that mosquito cell-derived alphaviruses actively suppress IFN-␣/␤ induction but that we were unable to detect this effect or that different results in other cell types, such as macrophages or human DCs, may be observed. For example, C6/36-derived WNV actively suppresses receptor-interacting protein 1 (RIP-1) signaling in murine macrophages (1). Additional reports demonstrated that the level of IFN-␣/␤ produced in plasmacytoid DCs infected with C7/10-cell derived WNV is drastically reduced compared to that produced in cells infected with Vero cellderived WNV but that C7/10-cell derived WNV is not able to actively inhibit IFN-␣/␤ induction by Sendai virus (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,27,29 In vitro studies involving mice and humans have demonstrated that WNV infection suppresses macrophage function by inhibiting the production of proinflammatory and antiviral cytokines. 2,18 American crows had moderate to severe splenic lymphoid necrosis, and there was abundant WNV antigen in both the red pulp and the white. The areas of mild to moderate necrosis in the pancreas consistently contained abundant viral antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Although the genetic basis of the relative attenuation of WNV KUN remains a topic of further study, the phenotype is at least partially due to a reduced ability to antagonize IFN signaling and/or the antiviral activity of specific ISGs. Amino acid substitutions between both viruses are dispersed throughout the genome, with differences in the viral proteins NS1, NS2A, NS2B, NS4A, NS4B, and E of WNV NY99 and WNV KUN identified as possible antagonists in IFN production or signaling (1,(15)(16)(17)(18)(19)24). Recently, WNV NY99 but not WNV KUN NS5 has been identified as a potent inhibitor of IFN-dependent JAK-STAT signaling; remarkably, a single-amino-acid substitution in WNV KUN NS5 restored the inhibitory activity to that observed for WNV NY99 NS5 (15).…”
mentioning
confidence: 99%